ANALISA PERBANDINGAN METODE FUZZY LOGIC CONTROL DAN METODE VIRTUAL FORCE FIELD (VFF) UNTUK DYNAMIC OBSTACLE AVOIDANCE - Asmak, Shochibah Yatimatul; Widyantara, Helmy; Puspasari, Ira (Journal of Control and Network Systems, 2015)
Technology today has reached its advancements even in military field. Technology in this field is often utilised to make tasks easier, to overcome human errors, as well as to do high-risk tasks that seem to be impossible to be done by human beings. High tech equipments are highly required to support offense and defense of the nation as well as to diminish human losses. One of the most prominent equipments in military field is combat vehicle. Thus, combat vehicles that can adapt quickly to any unknown environments are necessary and should there be obstacles, they could evade and find alternative routes to reach a designed target.Before such technology is created, a simulation using a robot is administered. In this simulation, the robotâs movements are observed. The observation includes how the robot evades obstacles especially moving obstacles and reaches the target successfully. There has been a prior research using Fuzzy Logic Control to control the robotâs speed and determine the evading direction when it encounters obstacles. Nevertheless, that research was only tested to evade unmoving obstacles. In this research, there would be comparative analysis between Fussy Logic Control and Virtual Force Field (VFF) method to evade moving targets as well as the ability to reach the designed targets.Â  There are two parameters used and analyzed in this research. They are the distance between the robot and the target and time required for the robot to reach the target. Those two parameters would be calculated using Fuzzy Logic Control and Virtual Force Field (VFF) method and the result would be compared to see which one is more effective to be used in this simulation.Keywords : Simulation Robot, Fuzzy Logic, Virtual Force Field, VFF, Dynamic Obstacle Avoidance